2000
DOI: 10.1023/a:1008117410827
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Rotating-wall vessels are beneficial to tissue engineering in that the reconstituted tissue formed in these low-shear bioreactors undergoes extensive three-dimensional growth and differentiation. In the present study, bovine corneal endothelial (BCE) cells were grown in a high-aspect rotating-wall vessel (HARV) attached to collagen-coated Cytodex-3 beads as a representative monolayer culture to investigate factors during HARV cultivation which affect three-dimensional growth and protein expression. A collagen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 37 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…Aggregate formation depends on cell type i.e. the ability of cells to grow in multiple layers, and on the dynamic conditions of the culture (Muhitch et al 2000 ). Early observations suggest that cell-microcarrier aggregate formation negatively affects growth of human mesenchymal stem cells (Chen et al 2013 ; Caruso et al 2014 ; Goh et al 2013 ) and we assume that myoblasts behave similarly.…”
Section: Discussionmentioning
confidence: 99%
“…Aggregate formation depends on cell type i.e. the ability of cells to grow in multiple layers, and on the dynamic conditions of the culture (Muhitch et al 2000 ). Early observations suggest that cell-microcarrier aggregate formation negatively affects growth of human mesenchymal stem cells (Chen et al 2013 ; Caruso et al 2014 ; Goh et al 2013 ) and we assume that myoblasts behave similarly.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that spontaneous aggregation of hAMSCs-laden CultiSpher S microcarriers in spinner flasks is common, which suggests an intrinsic mechanism of assembling for cell-laden microcarriers [13] . It has been suggested that the aggregation process is cell- and microcarrier-type dependent, possibly relying on cell proliferation, migration, ECM production and microcarrier property [25] [27] . In addition, by controlling culture condition, aggregates within an appropriate size can be made to ensure high cell viability [15] .…”
Section: Discussionmentioning
confidence: 99%
“…However, cells experience sheer force generated by continuous motion of the stirring bar, which adversely affects cellular physiology (Lin et al , 2008). Rotating flasks function similarly to the spinner flasks, but instead of using a stirring bar to keep the cells in suspension, the culture flask itself is rotated causing the cells to experience less force (Goodwin et al , 1993; Muhitch et al , 2000). Moreover, rotational speed of the flasks can be adjusted to obtain spheroids of desired sizes.…”
Section: Techniques For Generating Mctsmentioning
confidence: 99%